The social aspect of the diagnosis and clinical picture of postnatal depression in women - Turegeldieva, A. S.; Amitov, S. A. (ҚазҰУ Хабаршысы. Психология және әлеуметтану сериясы, 2020)
This article discusses the types of female depression in the postnatal period. The factors of the oc- currence of postnatal depression are investigated, its symptoms are systematized, the clinical picture of its manifestation is revealed. A woman in the period of postnatal depression feels dissatisfaction with her life, the quality of life changes dramatically, becoming negative. A feeling of helplessness, despair fills all spheres of life. The usual routine is violated, which prevents us from adequately perceiving reality, think- ing, and acting. Manifestations of postnatal depression significantly affect not only the woman herself, but also her child, her other children, her husband, i.e. for the whole family. One of the strongest symp- toms is also a feeling of social isolation among women who have given birth, loss of life in society, and a feeling that “life passes by.” The article also provides recommendations for the prevention of postnatal depression. Recommendations and conclusions can be used in practical work with pregnant and already given birth women, as well as in the process of training social workers. Key words: postnatal depression. clinical picture, social aspect, social isolation, social worker.